A comparative cost analysis of the Vaccination Program for US-bound Refugees. Issue 20 (11th May 2018) - Joo, Heesoo; Maskery, Brian; Mitchell, Tarissa; Leidner, Andrew; Klosovsky, Alexander; Weinberg, Michelle
Highlights: Vaccination Program for US-bound Refugees (VPR) provides selected vaccines overseas. VPR reduces vaccination costs for refugees across all age groups. Net savings per person vary from $226 (Medicaid rates for domestic costs) to $498 (private sector). Annual cost savings with VPR are $15.8–34.9 million (Medicaid-private sector) for 70 K refugees. VPR reduces risks of refugees with potential for vaccine-preventable diseases outbreaks in the US. Abstract: Background: Vaccination Program for US-bound Refugees (VPR) currently provides one or two doses of some age-specific Advisory Committee on Immunization Practices (ACIP)-recommended vaccines to US-bound refugees prior to departure. Methods: We quantified and compared the full vaccination costs for refugees using two scenarios: (1) the baseline of no VPR and (2) the current situation with VPR. Under the first scenario, refugees would be fully vaccinated after arrival in the United States. For the second scenario, refugees would receive one or two doses of selected vaccines before departure and complete the recommended vaccination schedule after arrival in the United States. We evaluated costs for the full vaccination schedule and for the subset of vaccines provided by VPR by four age-stratified groups; all costs were reported in 2015 US dollars. We performed one-way and probabilistic sensitivity analyses and break-even analyses to evaluate the robustness of results. Results: Vaccination costs with the VPR scenario were lower than costs of the scenario without the VPR for refugees in all examined age groups. Net cost savings per person associated with the VPR were ranged from $225.93 with estimated Refugee Medical Assistance (RMA) or Medicaid payments for domestic costs to $498.42 with estimated private sector payments. Limiting the analyses to only the vaccines included in VPR, the average costs per person were 56% less for the VPR scenario with RMA/Medicaid payments. Net cost savings with the VPR scenario were sensitive to inputs for vaccination costs, domestic vaccine coverage rates, and revaccination rates, but the VPR scenario was cost savings across a range of plausible parameter estimates. Conclusions: VPR is a cost-saving program that would also reduce the risk of refugees arriving while infected with a vaccine preventable disease.